Penerapan Aplikasi Media Pembelajaran pada SMP N 1 Nusawungu Berbasis Smartphone Android - Gustin Setyaningsih; Muhamad Awiet Wiedanto Prasetyo; Debby Ummul Hidayah (Universitas Bumigora, 2019)
Sekolah Menengah Pertama 1 Nusawungu for Biology Subject there are several sub-subject of material that are difficult to be presented directly, one of which is material for growth and development, the motion system, respiratory system, ciculatory system and photosynthesis system. From material that cannot be presented directly, the teacher must have new media in delevering biological material and students are facilitated in receiving the material from the teacher. In that case researchers have the aim of implementing mobile android-based learning media with the Multimedia Development Life Cycle method which consist of six stages in the from concept, design, material collecting, assembly, testing and distribution. Base on the results obtained by using a questionnaire, the appearance of learning media obtained a score of 82%, in terms of ease use learning media get 82,6%, in terms of understanding content biological material get 80% and in terms of effectiveness learning media help the learning process get 82,6%. So it can be concluede that learning media can help teachers and students in the teaching and learning process.